Analisis Peran ICC dalam Penuntutan Kejahatan Siber Crime Internasional dalam Praktik Hukum Pidana Internasional: Analisis Peran ICC dalam Penuntutan Kejahatan Siber Crime Internasional dalam Praktik Hukum Pidana Internasional - Mohamad Ali (CV Rewang Rencang, 2024)
Cybercrime has become a significant threat in the digital era, affecting global security, economic stability and human rights. The cross-border nature of cybercrime often exceeds the ability of national jurisdictions to deal with it, creating the need for effective international mechanisms. It found that, although the Rome Statute does not yet cover cybercrime, there is an opportunity to include this crime as part of future developments in international criminal law. This research will analyze Benefits at the International Criminal Court (ICC) in prosecuting international cyber crimes in the context and international criminal law. Because cybercrime is increasingly complex and occurs across borders, and has become a significant global challenge. However, to date, the Rome Statute which is the legal basis for the ICC has not explicitly covered cyber crimes as other major crimes against international states, examples crimes against genocide, crimes against humanity and crimes In against war or crimes of aggression. This research explores in potential role of the ICC in dealing with cyber crimes through interpretation of current international criminal law.